2022
DOI: 10.3389/fphys.2021.715567
|View full text |Cite
|
Sign up to set email alerts
|

circHIPK3 Exacerbates Folic Acid-Induced Renal Tubulointerstitial Fibrosis by Sponging miR-30a

Abstract: Renal tubulointerstitial fibrosis is a common pathological feature of progressive chronic kidney disease (CKD), and current treatment has limited efficacy. The circular RNA circHIPK3 is reported to participate in the pathogenesis of various human diseases. However, the role of circHIPK3 in renal fibrosis has not been examined. In this study, we aimed to determine whether and how circHIPK3 might participate in the pathogenesis of renal fibrosis. Mice received a peritoneal injection of folic acid (250 mg/kg). Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…circRNA_010383 sponging miR-135a, circHIPK3 sponging miR-185, circEIF4G2 sponging miR-218, circ_0000491 sponging miR-455-3p, circLRP6 sponging miR-205, and circ_15698 sponging miR-185 contribute to cell death, extracellular matrix production, or renal fibrosis in diabetic nephropathy [ 32 37 ]. Our group reported that circHIPK3 aggravate renal tubulointerstitial fibrosis by regulating miR-30a [ 38 ]. In human kidney diseases, circRNAs have been profiled in exosomes isolated from serum and urine samples from patients with idiopathic membranous nephropathy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…circRNA_010383 sponging miR-135a, circHIPK3 sponging miR-185, circEIF4G2 sponging miR-218, circ_0000491 sponging miR-455-3p, circLRP6 sponging miR-205, and circ_15698 sponging miR-185 contribute to cell death, extracellular matrix production, or renal fibrosis in diabetic nephropathy [ 32 37 ]. Our group reported that circHIPK3 aggravate renal tubulointerstitial fibrosis by regulating miR-30a [ 38 ]. In human kidney diseases, circRNAs have been profiled in exosomes isolated from serum and urine samples from patients with idiopathic membranous nephropathy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…hTGF-β is a well-accepted as a stimulator to induce kidney tubular cells damage for investigating mechanisms in vitro study [ 27 ]. It is reported that cell death and fibrosis are increased in hTGF-β1-treated kidney tubular cells [ 28 , 29 ]. We founded that IL-18 mRNA was gradually upregulated in HK-2 cells from 12 to 48 h after hTGF-β stimulation analyzed by qPCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are better approaches such as artificial intelligence [ 17 ] and machine learning [ 18 ] that use convolutional neural networks trained to learn how to interpret the results of a given sample, reproducing the pathologist visual assessment [ 19 , 20 , 21 , 22 ], there are also more straightforward approaches such as image processing software. One of the most used is the free software ImageJ [ 13 , 23 , 24 , 25 , 26 , 27 ] and, more effectively, automated software such as CellProfiler™.…”
Section: Discussionmentioning
confidence: 99%